Mechanical HIFU and immune checkpoint inhibition: toward clinical implementation - Vera Mekers; Mirjam de Visser; Karijn Suijkerbuijk; Clemens Bos; Chrit Moonen; Roel Deckers; Gosse Adema (International Journal of Hyperthermia)
Objective: Immune checkpoint inhibition (ICI) has significantly advanced the field of immuno-oncology, yet not all patients benefit from this therapy. Combining ICI with other therapeutic modalities, including tumor ablation, is currently being explored as a method to enhance ICI efficacy. Mechanical High-Intensity Focused Ultrasound (M-HIFU) represents a promising tumor ablative therapy, inducing cavitation within the tumor, resulting in tumor cell destruction and the release of danger signals and tumor antigens, two key factors contributing to anti-tumor immune responses.Methods/Results: Preclinical studies on the impact of M-HIFU on the anti-tumor immune response are guiding the translational application of this technique in the clinical setting. This review provides a comprehensive overview of the current understanding of the effects of M-HIFU on the immune system. We report on the effect of M-HIFU on soluble immune modulators and immune cells in different preclinical models, and potential contributions to the anti-tumor immune response. We discuss clinical studies applying M-HIFU and studies that have combined ICI with other ablative therapies to draw parallels to clinical implementation of M-HIFU. Further, we will highlight essential questions that should be addressed in future clinical trials exploring the combination of M-HIFU and ICI in the clinical setting.Conclusion: Overall, this review offers guidance for the clinical implementation of combining M-HIFU with ICI and highlights key questions that remain to be addressed in first clinical studies.